Role of the double mutant at two positions D260E and Y230V of the epoxide hydrolase in soybean seeds - Minh, Nghiem Ngoc (Academia Journal of Biology, 2014)
The epoxide hydrolases (EHs) are widely distributed among many bodies, including bacteria, fungi, plants and animals. These enzymes are an interesting group of functionnally related enzymes that catalyse the addition of water molecule to an epoxide (oxirane moiety), producing the corresponding 1-2 diol. Recent studies have been provided valuable informations on the molecular structure of these enzymes, as well as the insight to the enzymatic mechanisms that involved. To characterize one of the active sites of the epoxide hydrolases (EH), the gene encoding a soybean EH was modified with the synthetic oligonucleotide primers including the mutated sequence. The double mutant EH was constructed containing both of D260E and Y230V mutants. This mutant EH was expressed in E. coli BL21 (DE3) by using the pRSET expression plasmid in the presence of pKY260 but not produced the soluble EH form. These results have suggested that perhaps the replacement both of the Asp position 260 by Glu and the Tyr position 230 by Val in the soybean EH has resulted in the change of its space structure and then has produced the insoluble form.